GE_GERICHTE C/312/2012 vom 27. September 2013 - GE Cour de justice (2013)
MESURE PROVISIONNELLE; MODIFICATION(EN GÉNÉRAL); DIVORCE; DROIT DE GARDE; RELATIONS PERSONNELLES; VISITE | CPC.317.1; CC.134.1; CC.273.1